Long term outcomes of pediatric Bipolar-I disorder: A prospective follow-up analysis attending to full syndomatic, subsyndromal and functional types of remission. (July 2022) - Wozniak, Janet; DiSalvo, Maura; Farrell, Abigail; Joshi, Gagan; Uchida, Mai; Faraone, Stephen V.; Cook, Emmaline; Biederman, Joseph
Abstract: Objective: To examine patterns of remission of pediatric bipolar I (BP-I) disorder attending to syndromatic, symptomatic, and functional outcomes from childhood to adolescent and young adult years. Methods: We analyzed data from a six-year prospective follow-up study of youths aged 6–17 years with BP-I disorder. Subjects were comprehensively assessed at baseline and subsequently at four, five, and six years thereafter. Assessments included structured diagnostic interviews and measures of psychosocial and educational functioning. Patterns of remission were calculated attending to whether syndromatic, symptomatic, and functional remission were achieved. Results: Kaplan-Meier failure functions revealed that the probability of functional recovery from pediatric BP-I disorder was very low. Of the 88 youths assessed, only 6% (N = 5) of the sample were euthymic with normal functioning during the year prior to their last follow-up assessment (average follow-up time = 5.8 ± 1.8 years). Conclusions: These results provide compelling evidence of the high level of persistence of pediatric BP-I disorder. Symptomatic and functional remission were uncommon and most subjects continued to demonstrate high morbidity into late adolescence and early adulthood. Highlights: Emerging evidence suggests that pediatric bipolar disorder persists over time. In assessing longitudinal course of pediatric bipolar disorder, functioning and subthreshold states should be included. Lower SES, preschool age of onset and severe impairment at baseline increase the odds of persistentpediatric mania.